LEGAL ISSUES OF KEEPING SUBSCRIBER NUMBER IN THE MOBILE RADIOTELEPHONE NETWORKS - K. V. Kostina (Russian Journal of Economics and Law)
The article investigates certain legal issues of keeping the subscriber number when changing the mobile operator in the Russian Federation, and suggests ways of their solution.